Optimization Design for Support Points of the Body-Mounted Solar Panel - Qingwu Liu; Jisong Yu; Zhenjia Wang; Hao Cheng; Shanbo Chen; Lei Zhang (Aerospace)
Body-mounted solar panels are extensively utilized in satellite construction due to their simple structure and robust vibration resistance. The quantity and arrangement of support points on the body-mounted solar panel significantly affect its natural frequency. Thus, the design of these support points is a crucial aspect of the design process for body-mounted solar panels. This study presents a method for determining the support points of body-mounted solar panels, enabling rapid and precise identification of the quantity and positioning of these points based on the stated natural frequency in the design. First, a new algorithm is proposed, based on the finite element method, to optimize the positioning of support points on the body-mounted solar panel without the need for remeshing. Utilizing this algorithm, the distinct impacts of support point positioning and stiffness on the natural frequency of the solar panel are investigated, and the practical principles are proposed for quickly and accurately identifying the optimal locations of support points to maximize the natural frequency of the solar panel, given a predetermined number of support points. Subsequently, based on Courant–Fischer’s theorem, a method to ascertain the least quantity of support points through two modal analyses is presented. By integrating the aforementioned principles and method, a two-step procedure for identifying the quantity and positioning of support points is developed. Ultimately, the proposed two-step procedure is implemented in the design of the solar panel of the Jilin-1XXX satellite. The modal test reveals that the natural frequency of the solar panel surpasses the design index criteria, hence validating the efficacy and feasibility of the optimal design technique for the support points of the body-mounted solar panel presented in this study.